Skin and heart histopathology in fatal electrocution with otherwise inconclusive autopsy findings: A case series - Das, Siddhartha; Toi , Pampa C h (Journal of Indian Academy of Forensic Medicine, 2021)
The macroscopic evidence of low voltage electrocution in the skin is seen in the form of a crater with raised areolar edges and a surrounding pale area. This typical picture ofskin is mostly minimal or altogether absent in many cases of electrocution. The issue gets complicated in the absence of any eye witnesses or circumstantial evidences. Under such a scenario, it is advisable to do a histopathological examination of the suspected skin wounds. Since cardiac arrest is the most common mechanism of death following electrocution, heart histopathology may also yield vital evidence. We report three cases of electrocution. In one case, there were eye witnesses to the electrocution incident. In the second case the body was recovered from a swimming pool with no direct eye witness. In the third case the victim suddenly collapsed while welding. All the three cases were received dead in our hospital with inconclusive skin findings during autopsy examination.The histopathological examination of heart along with the skin wounds provides the vital evidence in favor of electrocution. Through these case reports we stress the importance of histopathologically examining the skin and heart in alleged cases of electrocution with inconclusive autopsy findings.